The Adaptation of the Sonata in C minor for Cistre and Continuous instrument by Francesco Geminiani (1760) for Wire Baroque Guitar - Alves Souto, Luciano Hercilio [UNESP] (Univ Federal Goias, 2021)
This paper discusses the transcription of the sonata in C minor for cistre and continuous bass by Francesco Geminiani (1760) for wire baroque guitar, with the objective of investigating critical, analytical and transcriptive parameters essential for its adaptation. It addresses elements that need to be evaluated when changing notational and instrumental mediums such as technique, tonality, tuning, harmony, articulation, ornamentation and dynamics, in the light of primary and secondary sources such as Geminiani (1749-1760), Leite (1764), Sanz (1674), Ribeiro (1789), Cardoso (2014), Costa (2012) and Tyler (2011). The results provided contextualizing performances of Geminiani's musical thought in relation to the instrumental practice of that time.
Keywords: Francesco Geminiani; Sonata in C minor; String Instrument; Transcription